The association between self‐reported diet quality and health‐related quality of life in rural and urban Australian adolescents. (19th January 2016) - Bolton, Kristy A.; Jacka, Felice; Allender, Steven; Kremer, Peter; Gibbs, Lisa; Waters, Elizabeth; de Silva, Andrea
Abstract: Objective: This study examines the relationship between diet quality and health‐related quality of life (HRQoL) in rural and urban Australian adolescents, and gender differences. Design: Cross‐sectional. Setting: Secondary schools. Participants: 722 rural and 422 urban students from 19 secondary schools. Main outcome measures: Self‐report dietary‐related behaviours, demographic information, HRQoL (AQoL‐6D) were collected. Healthy and unhealthy diet quality scores were calculated; multiple linear regression investigated associations between diet quality and HRQoL. Results: Compared to urban students, rural students had higher HRQoL, higher healthy diet score, lower unhealthy diet score, consumed less soft drink and less frequently, less takeaway and a higher proportion consumed breakfast (P < 0.05). Overall, males had higher unhealthy diet score, poorer dietary behaviours but a higher HRQoL score compared to females (P < 0.05). In all students, final regression models indicated: a unit increase in healthy diet score was associated with an increase in HRQoL (unstandardised coefficient(B)±standard error(SE); B = 0.02 ± 0.01(SE); P < 0.02); and a unit increase in unhealthy diet scores was associated with a decrease in HRQoL (−0.01 ± 0.00; P < 0.05). In rural students alone, a unit increase in unhealthy diet score was associated with a decrease in HRQoL (B = −0.01 ± 0.00; P = 0.002), and in urban students a unit increase in healthy diet score was associated with an increase in HRQoL (B = 0.02 ± 0.00; P < 0.001). Conclusions: Cross‐sectional associations between diet quality and HRQoL were observed. Dietary modification may offer a target to improve HRQoL and general well‐being; and consequently the prevention and treatment of adolescent health problems. Such interventions should consider gender and locality.